Sistem Informasi Tracer Study Berbasis Web Mobile pada AMIK Luwuk Banggai (SI-Trast) - Erni Sambulaka; Ira Tulutano; Rezha Aimang; Moh. Akbar Rifai; Moh. Islam. D; Trisno Wibowo. K; Iskandar Surdin (Jurnal Publikasi Teknik Informatika, 2025)
Tracer studies are an important instrument used by universities to evaluate the quality of graduates and assess the relevance of the curriculum to the needs of the workforce. Information obtained from tracer studies can provide valuable input for improving the quality of education, developing study program development strategies, and meeting data requirements for accreditation. However, manual tracer study implementation often faces various obstacles, including limited respondent reach due to uneven questionnaire distribution, time-consuming data processing, and difficulties in presenting structured and easily understood reports. Based on these problems, this study aims to design and implement a web-based Tracer Study Information System at AMIK Luwuk Banggai. This system was developed to simplify the process of collecting, processing, and analyzing alumni data more efficiently and accurately. The research method used is Research and Development (R&D) with a Waterfall development model approach, which includes the stages of needs analysis, system design, implementation, and testing. The results show that the system is able to manage alumni data centrally, provide facilities for filling out tracer study questionnaires online, and produce reports in the form of informative tables and graphs. This feature helps the university present faster, more accurate, and more easily accessible data as a basis for strategic decision-making. Thus, the designed web-based tracer study information system has proven to be operational and functional as intended. Implementation of this system not only improves the efficiency and accuracy of tracer study implementation but also supports the institution's data needs for academic development and study program accreditation.